P322 Effectiveness of Tumor Necrosis Factor-alpha inhibitors and Thiopurines combination therapy according to, 6-thioguanine nucleotides plasma levels: A Systematic Review. (21st January 2022) - Céspedes Martínez, E; Robles, V; Miarons, M; Herrera-De Guise, C; Mayorga-Ayala, L; Perez, Z; Oller, E; Casellas, F; Borruel, N
Abstract: Background: Inflammatory bowel diseases (IBD), Crohn's disease (CD) and Ulcerative Colitis (CU), have a progressive course with a significant percentage of primary or secondary failure to anti- tumor necrosis factor (TNF). It is already known that the combination therapy with anti-TNF and thiopurines have shown more effectiveness than monotherapy, especially with Infliximab (IFX). Thiopurines activity optimization, by the, 6-thioguanine nucleotides (6-TGN) measurement, have been related to better clinical outcomes in monotherapy, but evidence is lacking regarding combination therapy. Our aim was assessing the clinical and pharmacokinetic outcomes of the combination therapy regarding (6-TGN) serum levels. Methods: We performed a systematic review in electronic resources in three major databases (PUBMED, Cochrane and Web of Science) up to, 18 January, 2021 using MeSH terms, text terms and specific outcomes without restrictions for year or language. We searched for randomized clinical trials (RCT) and observational studies. Outcomes included clinical remission, clinical relapse, mucosal healing, anti-TNF serum levels, antibodies to anti-TNF and adverse events regarding, 6-TGN serum levels. Studies without, 6-TGN measurement were excluded. Results: Our search identified, 14 studies (three RCT and, 11 observational studies). Eight (57.1%) studies in Crohn's disease patients. Seven (50.0%) publications included patients with IFX, and, 5 (35.7%) with adalimumab (ADA). Most of the studies showed a positive association between, 6-TGN serum levels and clinical remission in patients with IFX treatment. Higher, 6-TGN serum levels improved the pharmacokinetic profile in patients with both anti-TNF. The target, 6-TGN serum levels proposed for the pharmacokinetic outcomes were lower (125–200 pmol/, 8 ×, 10 8 RBC) than those for clinical remission (230 -, 450 pmol/, 8 ×, 10 8 RBC). Conclusion: This systematic review shows that adequate, 6-TGN serum levels are associated with clinical response and better pharmacokinetic outcomes in combination therapy with IFX, with a weaker association with ADA therapy. Lower, 6-TGN serum levels could be enough to avoid unfavorable pharmacokinetic evolution with anti-TNF, especially IFX. There is not enough data supporting lower thiopurines doses for clinical outcomes, nor even to avoid adverse events. Further, well-designed research is needed to confirm the importance of, 6-TGN monitoring to optimize the combination therapy with anti-TNF and to decrease thiopurine doses when possible.